Guide to writing - Glenn, Cheryl (Wadsworth Pub. Co, 2009)
"Includes the 2009 MLA Update"--Cover.; This book brings the rhetorical situation to life. Renowned author and educator Cheryl Glenn translates rhetorical theory into easy-to-follow (and easy-to-teach) techniques that help sharpen students' ability to observe what words, assertions, or opinions might work best with a particular audience in a specific situation.